Odpowiedzialny księgowy? - Koczar, Joanna (Responsible Accountant?, 2007)
The aim of this article is to formulate some necessary questions that not only accountants but also scientists should be asked. These questions are as follows: Is it necessary to introduce changes in Polish legal regulations relating to accountant's responsibility for accountancy? Is it possible to improve this situation without changes in law?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 101-106